PREMATURE SKIN AGEING: CLINICAL AND MORPHOLOGICAL CHARACTERISTICS (World Bulletin of Social Sciences, 2024)
During the human existence, the skin undergoes a strong process of morphological, structural and biochemical changes, which are manifested by thinning, inconsistent tone, hyperpigmented patches spots, loss of flexibility and decreased turgor